2020
DOI: 10.1002/ejhf.1853
|View full text |Cite
|
Sign up to set email alerts
|

Liver function and prognosis, and influence of sacubitril/valsartan in patients with heart failure with reduced ejection fraction

Abstract: The prevalence of liver function abnormalities is common in patients with heart failure (HF) with reduced ejection fraction (HFrEF). We assessed the impact of liver function on prognosis and the effect of sacubitril/valsartan on measures of liver function in patients with HFrEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…Abnormal liver function may lead to increased fluid overload due to hypoalbuminemia and low-osmolality state, which may lead to deterioration of heart failure. This explains the liver function indicators as powerful predictors of prognosis in patients with CHF comorbid with AF in our study, and is consistent with other studies [15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…Abnormal liver function may lead to increased fluid overload due to hypoalbuminemia and low-osmolality state, which may lead to deterioration of heart failure. This explains the liver function indicators as powerful predictors of prognosis in patients with CHF comorbid with AF in our study, and is consistent with other studies [15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…The heterogeneity of CHF patients resulting from pooling HFpEF and HFrEF could be a reason for these inconsistent results. A recent post-hoc analysis of the PARADIGM-HF trial found that ALT was associated with worse prognosis in chronic HFrEF patients, as well as TBIL, but not AST ( 29 ). Of note, as they included chronic HFrEF patients, some of them could be with bilateral HF.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of comorbidities varied with HF severity ( 5 ). As shown in Figure 1 , we summarized the prevalence of major comorbidities according to the different organs and systems involved, such as hypertension (65%), atrial fibrillation (45%), chronic obstructive pulmonary disease (COPD)/asthma(40%), iron deficiency (30%), diabetes (40%), chronic kidney diseases (CKD) (25%), obesity (45%) ( 6 , 7 ), ischaemic heart disease (50%), hyperlipidaemia (55%) ( 8 ), depression (40%) ( 9 11 ), sleep apnea (40%) ( 12 ), sarcopenia (40%) ( 13 ) and liver dysfunction (10%) ( 14 ). The high prevalence of multi morbidity is associated with poor prognosis and heavy heath burdens, and therapy for multi morbidity in HF is still a challenge ( 15 ).…”
Section: Introductionmentioning
confidence: 99%